Pengaruh Motivasi Kerja Terhadap Kinerja Mitra Pengemudi Gojek di Magelang Pada Masa Pandemi Covid-19 - Adiesta Maarij, Hafidz Adnin; Verawati, Dian Marlina (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This research is entitled "Effect Of Work Motivation On The Performance Of Gojek Driver Partner In Magelang During The Covid-19 Pandemic". The purpose of this study was to determine the effect of work motivation on improving the performance of Gojek driver partners in Magelang during the covid-19 pandemic. The research method chosen in this study is a descriptive qualitative method with data collection methods by interviews and observations. The results of this study indicate that the fulfillment of daily needs is the basis of motivation at work. Gojek driver-partners realize that improvements are needed in working to achieve goals. The performance results generated through increased performance are evidence of the effect of work motivation on the performance of Gojek driver partners in Magelang.